(untitled) (Signo y seña, 2017)
This paper deals with the use of two spatial adverbial constructions in Spanish: locative adverb + possessive pronoun (as in “delante suyo”), that alternates with the normative form locative adverb + [preposition de + personal pronoun] (as in “delante de él”). The study presents an overview of its historical and geographic distribution, a topic which has not been deeply approached before. The analyzed materials consist of the main three corpora of Spanish (CORDE, CREA and CORPES XXI). The starting point is that the construction with the possessive form is present in all Spanish speaking regions and that it alternates with the prepositional construction. Based on empirical data and earlier studies, this paper finds that the possessive construction can be found in almost all Spanish speaking regions, but that it was first used and has its origin in Peninsular varieties of Spanish and has the highest frequency of use in the River Plate region.